The role of Islamic financial engineering in dealing with financial crises - RECHAM, Kahina; DJEMIL, Ahmed (Journal of Human Sciences, 2020)
The financial crises, coupled with negative repercussions on the economies of countries, led to thinking about finding alternatives to overcome these effects as a result of the capitalist system, which necessitates the introduction of new mechanisms. The Islamic system finds itself as an alternative. Islamic Bank to provide precautionary measures to prevent and avoid financial crises. This paper attempts to define the concept of Islamic financial architecture and its characteristics, and to present the most important products of the financial engineering industry in Islamic financial institutions and their ability to deal with financial crises These products are the strength of Islamic economic policies derived from Islamic Sharia.